Study of the Spectroscopic Analysis, Electronic Structure and Thermodynamic Properties of Ethyl benzene Using First-Principles Density Functional Theory - Ghimire, Rabin; Magar, Abhishek Rana; Basnet, Bishwo; Uprety, Roshika; Pudasainee, Kiran; Rai, Krishna Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
This study describes the optimized molecular structure, spectroscopic analysis, electronic structure and thermodynamics properties of the ethylbenzene molecule using first-principles DFT/B3LYP method with 6-311++G(d,p) basis set. The C-H in-plane bending vibration is observed between 1400 and 1050 cm-1, while the C-H out-of-plane bending vibration is observed between 1000 and 675 cm-1. The benzene ring has the most negative potential that corresponds to the attraction of proton due to concentrated electron density while the moderate positive potential is localized closed to the hydrogen atom. Analysis of the HOMO and LUMO in ethylbenzene anticipates an energy disparity of 6.3028 eV, a value closely matching the energy gap derived from DOS calculations. Mulliken charge analysis of the ethylbenzene molecules gives the information that all the hydrogen atom corresponds to the positive charges while all the carbon atom except C3 corresponds to the negative charge and the values of the global parameters such as hardness, chemical potential, electronegativity, electrophilicity index, softness are found to be 3.1514 eV, -3.5979 eV, 3.5979 eV, 2.0538 eV and 0.3173 eV-1 respectively. Various thermodynamic parameters such as heat capacity at constant volume, heat capacity at constant pressure, total internal energy, enthalpy and entropy, exhibit a rising trend with increasing temperature whereas Gibbs free energy shows an inverse relationship with temperature variation.